EFEKTIVITAS MARKETING PUBLIC RELATIONS SEBAGAI IMAGE SUPPLY CHAIN PADA BRAND MIXUE - Jatayu hadi prakoso (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2023)
This study aims to determine the Marketing Public Relations Effectiveness of the Mixue brand as an image supply chain. Marketing public relations is an effort to provide useful information to raise public awareness of a product or brand so that consumers want to buy or collaborate on that product or brand. As well as supply chain, namely effective and efficient supply chain management will be able to increase competitive advantage within the company through efficiency in production and distribution costs as well as the accuracy of production costs to the end consumer. It can be concluded that the effectiveness of Marketing Public Relations cannot be separated from using the principles of the public relations mix. One of them is by setting a low price compared to other competitors. As well as supply chain elements from Mixue, namely ordering raw materials in large volumes, so that they can reduce prices quite significantly. Second, Mixue has a number of production facilities, such as a product research and development center to a logistics center that is able to serve the needs of all outlets and deliver them free of charge. And finally, the Mixing Method for profit is the Economic of Scale method, namely applying orders for raw materials in large quantities and getting cheaper capital. With this supply chain performance franchise, the more outlets, the greater the profit.